If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x(x+11)=-15
We move all terms to the left:
3x(x+11)-(-15)=0
We add all the numbers together, and all the variables
3x(x+11)+15=0
We multiply parentheses
3x^2+33x+15=0
a = 3; b = 33; c = +15;
Δ = b2-4ac
Δ = 332-4·3·15
Δ = 909
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{909}=\sqrt{9*101}=\sqrt{9}*\sqrt{101}=3\sqrt{101}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(33)-3\sqrt{101}}{2*3}=\frac{-33-3\sqrt{101}}{6} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(33)+3\sqrt{101}}{2*3}=\frac{-33+3\sqrt{101}}{6} $
| 3x+3+2x+187=360 | | − | | 2x-10=3x+10 | | -4=1x-4 | | -4-2x=-5x-13 | | 0f+2=8 | | 7g+16=37 | | 0.75x+10.50=13.50 | | 10-5x=40-25x | | v-(2v-3)=9 | | 4x-(3x-36+1)=10 | | 2-3(a+2)=9+a | | (98-47x)+25x-15+25+15+5x+50=360 | | -6f+2=8 | | 7x-3+2x=6 | | 3x+4x+9=23 | | Y(2y-27)=24 | | 12x-9+11x+3=180 | | 6+8f=6f | | -8(-8-7x)+5=349 | | 3-3.7f=10.3f+10 | | 12+4x+9x-8=40 | | (w)-10=-5 | | 10-5x=30-25x | | 4x(3x-36+1)=10 | | Y(2y-27)=0 | | 2x+16+4x+6=180 | | 19w-18w-(-w)+9w+4w=-15 | | 5x+3x-3=12 | | 4(2x+8)=2/3(18-6x) | | -3f+2=8-3f | | -y/6=-29 |